ECONOMIC VALUE ADDED AND MARKET VALUE ADDED ON STOCK PRICE - Desy Astrid Anindya; Muhammad Habibie (Jurnal Ekonomi, 2022)
This study aims to determine the effect of economic value added and market value added on stock prices. This study uses secondary data, with the research object of mining sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sample of the observations in this study amounted to 60 which was carried out using a purposive sampling method and processed by multiple linear regression analysis. The results of this study indicate that economic value added has a positive and significant effect on stock prices and market value added has a positive and significant effect on stock prices.